STUDI DISTRIBUSI POROSITAS, FASIES DAN TAHAPAN DIAGENESIS FORMASI JAMPANG DI NANGERANG, KABUPATEN SUKABUMI, PROV. JAWA BARAT. - Imron Hasani, Muhammad
Recently many volcanic reservoirs are produced and become proven reserve for hydrocarbons. However, many of these exploration process in volcanic environment faces major obstacle in understanding the reservoir itself. In order to get more understanding, analogs outcrops at Nangerang, Sukabumi Regency are being used. Analogs are being used to help understand the types of porosity, process of porosity formation and their diagenetic process and process that affected after diagenetic. There is hope that the understanding in exploration on volcanic fields in principle could be associated with this study . The methods are volcanostratigraphy and petrographyical analysis. Volcanostratigraphy analysis is carried out to determine the position, geometry, and deposit facies in lateral and vertical positions. 23 samples of petrography are carried out to determine the porosity type and their diagenetic process. The result shows 11 (eleven) volcanostratigraphy units, consisting of Basement Rock (1 unit), Jampang Khuluk (1 unit), Nangerang Khuluk (2 units), Bantarpanjang Khuluk (6) and Resedimented Unit (1 units). Using references s, the age of Basement Rock is Early Miocene Age and equivalent with Jampang Formation. Other volcanic units are estimated to be Late Miocene-Pliocene based on previous studies. Some of the samples have been taken by every position to be analyzed using petrographical analysis. The analysis shows that the matrix of pyroclastic breccia (flow deposit) and tuff (fall deposit) in all samples have primary porosity, composed of intergranular or intragranular. The appearance of dissolutionn/vuggy enhances the porosity of samples with the total of visible porosity 5%. Lateral analysis in deposit show that porosity is controlled by opaque mineral settling in matrix during eruption process, making central facies have lower porosity than distal facies. The genesis of dissolution vertically comes from weathering and alteration. However, some of samples shows that the alteration process decreasing the visible porosity because of quartz mineral filling.